2022
DOI: 10.1186/s13073-022-01072-4
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic prediction of antimicrobial resistance in critically ill patients with lower respiratory tract infections

Abstract: Background Antimicrobial resistance (AMR) is rising at an alarming rate and complicating the management of infectious diseases including lower respiratory tract infections (LRTI). Metagenomic next-generation sequencing (mNGS) is a recently established method for culture-independent LRTI diagnosis, but its utility for predicting AMR has remained unclear. We aimed to assess the performance of mNGS for AMR prediction in bacterial LRTI and demonstrate proof of concept for epidemiological AMR survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…For example, Huang et al employed a sequence-based assay to successfully detect human pathogens in 94.49% of samples from patients with pulmonary infections who had tested negative for pathogens using traditional pathogen detection methods. Their results thus demonstrated that sequence-based assay accuracy and sensitivity exceeded corresponding standard pathogen detection assay performance indicators [23]. Similarly, Wang et al found that their sequence-based assay was more sensitive than traditional methods for detection of mixed pulmonary infections [24], whereas Chen et al obtained sequence-based test results for BALF specimens collected from patients with severe PTB disease that closely aligned with standard culture method-based results [25].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Huang et al employed a sequence-based assay to successfully detect human pathogens in 94.49% of samples from patients with pulmonary infections who had tested negative for pathogens using traditional pathogen detection methods. Their results thus demonstrated that sequence-based assay accuracy and sensitivity exceeded corresponding standard pathogen detection assay performance indicators [23]. Similarly, Wang et al found that their sequence-based assay was more sensitive than traditional methods for detection of mixed pulmonary infections [24], whereas Chen et al obtained sequence-based test results for BALF specimens collected from patients with severe PTB disease that closely aligned with standard culture method-based results [25].…”
Section: Discussionmentioning
confidence: 91%
“…Second, since our research focused on BALF specimens, the collection of lavage specimens containing numbers of pathogenic bacteria below the detection level of the test may have resulted in false-negative results as a reminder that the nanopore sequencing assay is still an auxiliary tool that should be used in combination with clinical features, radiological imaging ndings, and laboratory test results to diagnose suspected PTB cases. Third, we could not rule out that false-negative and false-positive nanopore sequencing assay results occurred due to (1) a sequence depth that was too low; (2) high host genome background noise and low microbial pathogen biomass; (3) administration of antibiotics to patients prior to testing; and (4) contamination of samples with genomes of environmental microbes or human flora [23]. Fourth, the absence of certain control diseases, such as lymphomas and rheumatoid arthritis (rare diseases in patients of Beijing Chest Hospital), may have biased our results.…”
Section: Discussionmentioning
confidence: 99%
“…Although, mNGS provided a new strategy to predict resistance genes for inferring antimicrobial susceptibility 28 . Due to the low abundance of pathogen AMRs in respirators or body uids which hampered the AMRs detection by using mNGS 29 and predicted AMRs still remained more limited 25,30−33 . Our data also showed mNGS to detect AMRs was very low for limited coverage and sequencing depth of MTB, which was consistent with previous study 15 .…”
Section: Discussionmentioning
confidence: 99%
“…As clinical and academic teams came together through the unifying pandemic imperative [10], the translational research timeline for pathogen sequencing shortened. Diagnostic accuracy studies are beginning to demonstrate satisfactory performance with pathogen detection [11 ▪ ,12 ▪ ] and there are innovative approaches to detecting AMR elements using nanopore sequencing with cas9 enrichment [13 ▪ ] or predicting AMR using machine learning [14]. There is also increasing focus on clinical laboratory quality requirements including validation, reproducibility, setting limits of detection, and producing positive and negative internal controls and externally distributed reference materials for quality assurance [15].…”
Section: The Respiratory Metagenomics Propositionmentioning
confidence: 99%